Red dragon [videorecording (DVD)] - Ratner, Brett; Hopkins, Anthony, 1937-; Norton, Edward; Fiennes, Ralph; Keitel, Harvey; Watson, Emily, 1967-; Hoffman, Philip Seymour, 1967-2014; Parker, Mary-Louise; Harris, Thomas, 1940- (Universal, 2008)
Will Graham is an FBI agent who brought Hannibal Lecter to justice; however, his confrontation with Lecter proved to be a bloody, near-death experience. Retiring from the Bureau, he moves to Florida. However, a particularly grisly killer is on the loose, and Jack, Graham's one-time mentor at the Bureau, asks him to return to duty to find him. "The Tooth Fairy" is a vicious murderer who kills entire families at once, covering the eyes of his victims with bits of a shattered mirror.